PENGARUH KUALITAS PRODUK, PELAYANAN DAN HARGA TERHADAP MINAT KONSUMEN: PENGARUH KUALITAS PRODUK, PELAYANAN DAN HARGA TERHADAP MINAT KONSUMEN - Miftahul Khomsa AUlia Erwin; Pungky Soleha Millenianingsih; Lorinda Febriani; Abdul Muslim; Sugeng Suntoso (Administratif Profesional, 2022)
LMN Restaurant is one of the most popular noodle restaurants in Indonesia. Almost every branch is always filled with customers, and based on the results of researchers' surveys of customers, they know that the product is around 2020 to 2022, which we can know that in that year the world was hit by the Covid-19 pandemic. The specialty of LMN Restaurant itself is that this product has become booming after passing through the pandemic both on social media and topics of conversation. This study aims to analyze the effect of product quality, service quality and price on consumer interest in LMN Restaurants in the City of Jakarta. The quantitative approach is carried out by sampling using Purposive Sampling by distributing questionnaires to consumers. The analytical techniques used in this study are validity test, reliability test, normality test, multicollinearity test, coefficient of determination test (R2), F Anova test and multiple linear regression analysis. The results showed that product quality, service quality, and price have a positive effect on purchasing decisions. The results of this test show that products, services, and prices have a positive effect on consumer interest in buying LMN Restaurant products. From this study, the researcher gave advice in the form that researchers can further deepen what factors are needed by customers related to consumer interests and for price perceptions it is recommended to restaurants to pay attention to price competition and price suitability with product quality so as not to damage market competitiveness. Keywords: Product, Service, Price, Consumer Interest